2016
DOI: 10.20510/ukjpb/4/i5/134669
|View full text |Cite
|
Sign up to set email alerts
|

ABO/Rhesus Blood Group and Correlation with Sickle Cell Disease and Type-II Diabetes Mellitus in South East and South-South of Nigeria

Abstract: Correlation between ABO/Rhesus blood group, Sickle cell disease (SCD) and Diabetes mellitus (DM) was investigated in Okwe, Asaba, Delta State and Ihiala, Anambra State,Nigeria. 100 proven cases of sickle cell patients (HBSS) from the sickle cell clinic in the General Hospital, Okwe, Asaba, Delta State, Nigeria, were studied. 200 normal individuals, 100 with genotype AA and 100 with genotype AS were taken as control for comparison from Okwe town. Furthermore, 50 proven cases of adults diabetic mellitus type2 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Similarly, while carrying out the frequency of the blood group distribution among our cohort, it was revealed that O and A blood group individuals are mostly associated with genotype SS (SCD), followed by B, and the least prevalent is AB. Again, this agrees with the study performed by Alagwu et al [15].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, while carrying out the frequency of the blood group distribution among our cohort, it was revealed that O and A blood group individuals are mostly associated with genotype SS (SCD), followed by B, and the least prevalent is AB. Again, this agrees with the study performed by Alagwu et al [15].…”
Section: Discussionsupporting
confidence: 93%
“…We further determined that most patients with SCD had type O RhD+ blood and that this variable varied significantly between the two groups (P = 0.022). This result was consistent with the findings of Alagwu et al [30] who reported an O blood group frequency of 63% among Hb-ss patients. This finding could be explained by the fact that the O Rh+ blood group is the most prevalent group in humans.…”
Section: Discussionsupporting
confidence: 93%